2021
DOI: 10.1111/ssqu.13028
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 pandemic and government responses: A gender perspective on differences in public opinion

Abstract: The 2019 novel coronavirus disease (COVID-19) crisis has led to shutdowns of the cultural, associational, and economic life in many parts of the world and had a severe impact on gender relations in many societies. This study engages with gender differences in public support of severe infringements of personal and economic freedoms. Methods: We use data from an original survey conducted by CINT in the United States and Germany in June 2020. Descriptive statistics both aggregated for the two countries and then s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In line with the assumption posed in the previous lines, Alsharawy et al (2021) find that gender differences in COVID compliance disappear once perceptions of fear are controlled for, meaning that the gender gap in compliance with the norms is partly derived from women's higher risk perception associated with COVID-19. To the contrary, Stockemer et al (2021) found that there are only slight gender differences in health risk perceptions associated with , and yet women are significantly more supportive of strict restrictive measures than men (see also Galasso et al, 2020). In that case, the gender gap in compliance is not dependent on different assessments of risk by women and men.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In line with the assumption posed in the previous lines, Alsharawy et al (2021) find that gender differences in COVID compliance disappear once perceptions of fear are controlled for, meaning that the gender gap in compliance with the norms is partly derived from women's higher risk perception associated with COVID-19. To the contrary, Stockemer et al (2021) found that there are only slight gender differences in health risk perceptions associated with , and yet women are significantly more supportive of strict restrictive measures than men (see also Galasso et al, 2020). In that case, the gender gap in compliance is not dependent on different assessments of risk by women and men.…”
Section: Introductionmentioning
confidence: 97%
“…Citizens’ levels of compliance with these restrictive measures has varied (Lin et al., 2021 ) and in some contexts were highly modulated by ideology and political sympathies (Becher et al., 2021 ; Gonzalez et al., 2021 ; Wu and Huber, 2021 ). One common finding cross‐nationally is that there is greater compliance with the restrictive measures established as a consequence of the COVID‐19 breakout among women than among men (Bronfman et al., 2021 ; Chuang and Liu, 2020 ; Clark et al., 2020 ; Galasso et al., 2020 ; Stockemer et al., 2021 ), even if men are more likely to suffer worse health consequences from COVID‐19 than women (Islam et al., 2020 ; Peckham et al., 2020 ). These gender differences seem to be partly related to gender differences in risk attitudes (Guenther et al., 2021 ; Lewis and Duch, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As controls, we included age (Survey1), knowing that the increased risk of older people made them more supportive of measures (Lilleholt et al, 2020, Sabat et al, 2020, gender (both) considering that male were less concerned about (Lewis & Duch 2021) and less supportive of stringent measures (Stockemer et al, 2021); education (both) related to different media consumption patterns and knowledge about the COVID-19; subjective social class (Survey2) as a possible marker of social inferiority (see again Hochschild, 2016;Inglehart & Norris, 2017); unemployment (Survey1) as a possible hardship, having additional impact on support for the measures beyond financial difficulties due to COVID-19; general frequency of internet use (Survey2) as a demonstration of the respondent's propensity for digital media use; political interest (Survey2) as a control for trust in and knowledge of the political system; and political alignment (Survey2), following the research relating right-wing political orientation and conservatism to lower levels of compliance with pandemic control measures (Barbieri & Bonini Gonzalez et al, 2021;Becher et al, 2021;Wu & Huber, 2021).…”
Section: Beyond Descriptives: Does the Hypothesis Of Social Media Inf...mentioning
confidence: 99%